The Effect Of Work Life Balance, Cooperation, Communication And Fingerprint Attendance On Employee Performance - Indra Sakti; Ichsan Kurnia Saputra (Jurnal Ekonomi, 2024)
This study has to determine the effect of work-life balance, cooperation, communication and fingerprint attendance on the performance of tribal employees of the Water Resources Office of Johar Baru District. The strategy used in this study is a quantitative research strategy with multiple linear regression method. The population and sample in this study were 46 employees of the Johar Baru Subdistrict Water Resources Office using a saturated sampling technique of all 46 employees. The data collection technique used is to distribute questionnaires. Instrument testing uses validity and reliability tests. Hypothesis testing using partial correlation coefficient test (t test), coreal coefficient test, simultaneous regression coefficient test (F test) and partial and simultaneous determination test ( ). Using the SPSS 27.0 software data processing program. The results of the study partially stated that the variable of work life balance was positive and significant on employee performance variables, cooperation variables had a positive and significant influence on employee performance variables, communication variables had a negative influence on performance variables and  Fingerprint Attendance  variables had a negative influence on performance variables. In terms of coefficient of determination ( ) variables Work life balance, Communication, Cooperation and Fingerprint Attendance  have an influence of 66.2% on performance and the remaining 33.8% are influenced by other variables.